Concentrações salivares de cortisol, desidroepiandrosterona (DHEA) e variáveis psicológicas em pacientes com ulceração aftosa recorrente - Michel, Anete Rejane (2011)
Recurrent aphthous ulceration (RAU) is one of the most prevalent disease of the oral mucosa, but the mechanism that leads to the development of this lesion remains unknown. Psychological changes such anxiety and stress have been investigated and appear to exhibit, in some patients, an association with the disease. Stress causes dysregulation of the immune system and is related to elevated levels of cortisol and a decrease in dehydroepiandrosterone (DHEA) levels. In the present study, patients with RAU were investigated with regard to stress and anxiety levels, as well as salivary concentrations of the hormones cortisol and DHEA. The sample consisted of 60 individuals of both sexes, aged between 18 and 50 years and distributed into two groups: 30 patients with RAU and 30 patients without history of the disorder, matched by sex and age. Stress symptoms were assessed using the Lipp s Inventory of Stress Symptoms (LISS) and for anxiety the Beck Inventory of Anxiety (BAI). The saliva specimens were collected in the morning, in the afternoon and at night on the same day. In the RAU group, the specimens were collected on two occasions, in the presence and after remission of the lesions. The salivary concentrations of cortisol and DHEA were determined in duplicate by radioimmunoassay with a specific analytical kit for each hormone. The case patients exhibited higher anxiety scores (p=0.001), besides a greater prevalence of stress (p=0.004). Cortisol levels were significantly higher in the case group in the presence of the lesion in the morning (p=0.008) and afternoon (p=0.001) when compared to the same RAU patients in remission. The cortisol/DHEA ratio was also higher in the case patients in the presence of lesions when compared to the remission phase in the afternoon (p=0.007). There was no significant difference in DHEA levels between the groups. Based on the results obtained, it can be concluded that, in the sample investigated, stress and anxiety are more elevated in patients with RAU. In these individuals, salivary cortisol levels were increased in the presence of lesions, but did not differ when compared to the patients without the disorder. DHEA levels did not differ in patients with RAU in the presence or in remission of the lesion, or between RAU patients and control patients. There is a need for further studies to determine whether stress and anxiety, as well as elevated cortisol levels, have an influence on the etiopathogenesis of recurrent aphthous ulceration.